Religious Orientation (Internal and External) Effects on Aged Mental Health - Fazel Bahrami; Abbas Ramezani-Farani (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: The purpose of present study is to investigate "religious orientation (internal and external) effects on aged mental health". Materials & Methods: In an expost-facto and correlational study 230 male and female residents of elderly centers affiliated to welfare organization and public places (such as mosques and park) in which the non-resident aged persons gather, were selected through clustered randomized sampling. َAt first, the subjects were screened from cognitive disorders. Then, they completed GHQ-28, Beck Depression Inventory and Religious Attitude Test. The data were analysed through Pearson correlatioal Test and Mann-Whitney. Results: The results revealed that there is a significant correlation between elder depression and mental health. In the other words, the higher scores on external religious orientation, the higher scores on mental health problems and rates of depression. The more trends toward internal religious orientation, the lower rate of depression and mental health problems. Also, there was a meaningfull correlation between elder religious orientation and their mental health and depression rate. In other words, there was a meaningful correlation between mental health and depression rate of resident and non- resident elders. In addition women had more external religious orientation, while men had higher rates of internal religious orientation.  Conclusion: External religious belief had meaningful correlation with mental disorders and depression, and internal religious belief had meaningful correlation with mental health. Mental disorders and depression are more prevalent among resident elder than the non-residents, and also the resident elders have more external religious orientation.